Designing Assessments and Tools for your Program - Robert D. Garrick PhD (Academic Chairpersons Conference Proceedings, 2018)
Presenters and participants will discuss strategies and best practices available to chairs to involve faculty and external constituents in defining student learning outcomes (SLO), direct assessments and a process/department culture of continuous improvement.
Keywords: Assessment; learning outcomes; direct assessments; curriculum map; rubrics/scoring guides